2013
DOI: 10.1016/j.jvs.2012.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in conformability of the latest generation of thoracic stent grafts

Abstract: The requirement for close conformability has influenced the design of next-generation devices. Manufacturers have modified devices and/or their deployment system to specifically address this problem. When compared with the results of our previous experimental test, this study demonstrates that these alterations have resulted in a marked improvement in the performance of commercially available stent graft systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…However, the enhanced conformability of the last generation of thoracic stent-graft has significantly decreased the rate of stent-graft collapse. 23,24 Several therapeutic options can be proposed: the stentgraft can either be removed via an open thoracotomy or be re-expanded by an endoluminal approach. Open repair should be considered in cases of severely collapsed stent graft and/or deemed at high risk of coverage of supra-aortic trunks owing to a severely angulated aortic arch.…”
Section: Discussionmentioning
confidence: 99%
“…However, the enhanced conformability of the last generation of thoracic stent-graft has significantly decreased the rate of stent-graft collapse. 23,24 Several therapeutic options can be proposed: the stentgraft can either be removed via an open thoracotomy or be re-expanded by an endoluminal approach. Open repair should be considered in cases of severely collapsed stent graft and/or deemed at high risk of coverage of supra-aortic trunks owing to a severely angulated aortic arch.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical data have shown that poor endograft apposition within the aortic arch increases the risk of technical failure after TEVAR [ 6 8 ]. The requirement for enhanced conformability has influenced the design of next-generation devices [ 9 ]. In November 2009, the Conformable TAG Thoracic Endoprosthesis (CTAG; W. L. Gore & Associates, Inc., Flagstaff, USA) received CE mark approval for TEVAR in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…5 The angle between the inner curvature of the aortic arch and the stent graft depends on the stent graft, the patient's age, and the cardiac phase. 6,7 Younger people often present with a tighter so-called gothic arch in contrast to the wider aortic arch to normally found in older people. Variation of the angle over the cardiac cycle has been reported as high as 20 (minimum in the diastole and maximum in the systole), 8 likely causing the risk of a stent graft compression syndrome with subsequent high aortic occlusion.…”
mentioning
confidence: 99%